2022
DOI: 10.1152/ajpheart.00322.2022
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes facilitate intercellular communication between uterine perivascular adipose tissue and vascular smooth muscle cells in pregnant rats

Abstract: Perivascular adipose tissue (PVAT) is distinct from other adipose depots as it has differential gene and protein profiles and vasoactive functions. We have shown that pregnancy affects the morphology of PVAT surrounding the uterine arteries (utPVAT) differentially than the morphology of non-perivascular reproductive adipose depots (i.e., periovarian adipose tissue, OVAT). Here, we hypothesized that pregnancy modifies the profile (size and molecular weight) of exosome-like extracellular vesicles released by utP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…FBS was depleted of exosomes via ultracentrifugation (Thermo Scientific, Sorvall WX + Ultra Series) at 10,000 xg for 2 hours as previously described(21). The exosome-depleted FBS aqueous layer was then filtered through a 0.2 μm-sized 50-mL tube top vacuum filter system (cat# 430320, Corning, NY).…”
Section: Methodsmentioning
confidence: 99%
“…FBS was depleted of exosomes via ultracentrifugation (Thermo Scientific, Sorvall WX + Ultra Series) at 10,000 xg for 2 hours as previously described(21). The exosome-depleted FBS aqueous layer was then filtered through a 0.2 μm-sized 50-mL tube top vacuum filter system (cat# 430320, Corning, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, uterine PVAT secretes exosome-like extracellular vesicles that are taken up by adjacent vascular smooth muscle cells [155]. Uterine PVAT-derived exosomes increase in size with pregnancy and carry proteins of greater molecular weight compared to uterine PVAT-derived exosomes from nonpregnant rats [155]. The exact mechanisms underlying the trafficking of uterine PVAT-derived exosomes to vascular smooth muscle cells and its effects on the function of the maternal uterine artery wall are currently unknown.…”
Section: Pregnancy and Vasoactive Effects Of Perivascular Adipose Tissuementioning
confidence: 99%
“…Although the exact mechanisms by which uterine PVAT attains these vasoactive effects remain unknown, we demonstrated that uterine PVAT potentiates the release of thromboxane B 2 from uterine arteries, although inhibition of thromboxane receptor did not abolish the antidilatory effects of uterine PVAT on isolated uterine arteries [154]. Interestingly, uterine PVAT secretes exosome‐like extracellular vesicles that are taken up by adjacent vascular smooth muscle cells [155]. Uterine PVAT‐derived exosomes increase in size with pregnancy and carry proteins of greater molecular weight compared to uterine PVAT‐derived exosomes from nonpregnant rats [155].…”
Section: Pregnancy and Vasoactive Effects Of Perivascular Adipose Tissuementioning
confidence: 99%
“…Interestingly, these modifications were restricted to uterine PVAT, while the periovarian adipose-tissue-derived EV profile was unchanged. These alterations modified EV morphology and cargo, with smaller vesicles of higher density in pregnant female rats, although the functional consequences for VSMC and vasorelaxation remain to be explored [65].…”
Section: Cardiovascular Effects Through Vascular Implicationsmentioning
confidence: 99%